Determination of Modelling Error Statistics for Cold-Formed Steel Columns - R. P. Rokade; K. Balaji Rao; B. Palani (Advances in Civil Engineering)
In this article, an attempt has been made to estimate the Modelling Error (ME) associated with compression capacity models available in international standards for different failure modes of compression members fabricated from Cold-Formed Steel (CFS) lipped channel sections. For the first time, a database has been created using test results available in the literature for compression capacities of CFS lipped-channel sections. The database contains details of 273 numbers of compression member tests which have failed in different failure modes, namely, (i) flexural, torsional, flexural-torsional, local, and distortion buckling and (ii) failure by yielding. Only those sources, which report all the details, required to compute the capacities using different standards are included in the database. The results of experimental investigations carried out at CSIR-Structural Engineering Research Centre, Chennai, are also included in this test database. The international codes of practice used in calculation of compression capacities of the database columns considered in this paper are ASCE 10-15 (2015), AISI S100-16 (2016), AS/NZS 4600: 2018 (2018), and EN 1993-1-3:2006 (2006). The ASCE, AISI, AS/NZS, and EN design standards have different design guidelines with respect to the failure modes, e.g., ASCE 10-15 (2015) standard provides stringent criteria for maximum width to thickness ratio for stiffened and unstiffened elements. Hence, guidelines for the distortional buckling mode are not provided, whereas the AISI S100-16 (2016) and AS/NZS 4600: 2018 (2018) standards consider separate guidelines for distortional buckling mode and EN 1993-1-3:2006 (2006) standard considers combined local and distortional buckling mode. Further, the sample size for each design standard is varying depending on the design criteria and failure mode. Studies on statistical analysis of ME suggest that the compression capacity predicting models for flexural-torsional buckling mode are associated with large variation irrespective of the design standard. Similar observations are made for the flexural buckling model as per EN 1993-1-3:2006 (2018) standard and distortional buckling models as per AISI S100-16 (2016) and AS/NZS 4600: 2018 (2018) standards. The compression capacities for test database sections are evaluated by neglecting the partial safety factors available in design standards. The probabilistic analysis to determine statistical characteristics of compression capacity indicates the importance of consideration of ME as a random variable. Hence, the ME results will be useful in code calibration studies and may have potential reference to design practice.